Microcystic adnexal carcinoma of the cheek-a case report with dermatoscopy and dermatopathology - Mike Inskip; Jill Magee (Mattioli1885, 2015)
We present a case report of a microcystic adnexal carcinoma on the cheek of a 67-year-old man. Clinical, dermatoscopic and dermatopathologic images are presented. A search of the literature has not discovered any previously published dermatoscopy images of microcystic adenexal carcinoma.